Do pain management websites foster self-management support for people with persistent pain? A scoping review. Issue 9 (September 2019) - Devan, Hemakumar; Perry, Meredith A.; van Hattem, Angelique; Thurlow, Greg; Shepherd, Sam; Muchemwa, Carol; Grainger, Rebecca
Highlights: It is unknown if websites provide information on skills to self-manage persistent pain. Currently 27 websites provide information for developing persistent pain management strategies. Six websites had comprehensive information supporting the development of self-management skills. One website provided culturally tailored information. Six of the twenty seven websites had a health verification certificate. Abstract: Objectives: To evaluate if the contents of pain management websites include the current best practice self-management support strategies for people with persistent pain, are cultural tailored and to determine the website quality. Methods: Websites were searched from three major search engines (Google, Bing, and Yahoo). Websites providing information on self-management strategies and websites that were freely available to the public were included. The website contents were evaluated using a 14-item self-management support (SMS-14) checklist. Website quality was assessed using the Health On the Net code (HONcode) certification. Results: Of the twenty-seven websites evaluated, the websites scored a median of nine items (range 1–13) from the SMS-14 checklist. The websites LivePlanBe, ACI Pain Management Network and MyJointPain top-scored (13/14) from the SMS-14 checklist. One website (ACI Pain Management Network) provided culturally tailored information and HONcode certification was present in six websites. Conclusions: The review identified 27 contemporary pain management websites that could be used for self-management skills training. Practice Implications: Clinicians could refer people with persistent pain to top ranked websites - LivePlanBe, ACI Pain Management Network, and MyJointPain for enabling self-management skills, with the caveats that most websites lacked cultural tailoring, and have limited or no evidence of clinical efficacy.